High room-temperature optical gain in Ga(NAsP)/Si heterostructures - Koukourakis, Nektarios; Gerhardt, Nils Christopher; Hofmann, Martin; Bückers, Christina; Funke, Dominic A.; Liebich, Sven; Chatterjee, Sati Nath; Lange, Christoph; Zimprich, Martin; Volz, Kerstin; Stolz, Wolfgang; Kunert, Bernardette; et al. (Applied physics letters)

Magnetic field dependence of the spin relaxation length in spin light-emitting diodes - Höpfner, Henning; Ludwig, Arne; Ludwig, Astrid; Reuter, Dirk; Wieck, Andreas; Gerhardt, Nils Christopher; Hofmann, Martin; Fritsche, Carola; Stromberg, Frank; Wende, Heiko; Keune, Werner (Applied physics letters)

Depth-filtered digital holography - Koukourakis, Nektarios; Jaedicke, Volker; Adinda-Ougba, Adamou; Gerhardt, Nils Christopher; Hofmann, Martin; Goebel, Sebastian; Wiethoff, Helge; Höpfner, Henning (Optics express)

Signal processing for spectroscopic optical coherence tomography - Jaedicke, Volker; Agcaer, Semih; Kasseck, Christoph Tobias; Gerhardt, Nils Christopher; Hofmann, Martin; Goebel, Sebastian; Welp, Hubert (Proceedings of the 7th International Workshop on Biosignal Interpretation (BSI2012))

Multispectral photoacoustic coded excitation using pseudorandom codes - 82231E - Beckmann, Martin; Friedrich, Claus-Stefan; Mienkina, Martin; Gerhardt, Nils Christopher; Hofmann, Martin; Schmitz, Georg (Photons plus ultrasound)

Regularity properties of infinite-dimensional Lie groups, and semiregularity - Glöckner, Helge

Weighted diffeomorphism groups of Banach spaces and weighted mapping groups - Walter, Boris (Dissertationes Mathematicae)
Keywords: 58D05; 22E65; 22E67; 26E15; 26E20; 46E10; 46E40; 46E50; 46T05; 46T10; 46T20; 58D15

Upper bounds for continuous seminorms and special properties of bilinear maps - Glöckner, Helge (Topology and its Applications)
Keywords: 46A03; 46F05; 22D15; 42A85; 46A11; 46A32

Topological algebras of rapidly decreasing matrices and generalizations - Glöckner, Helge; Langkamp, Bastian (Topology and its Applications)
Keywords: 46H20; 46A45; 22E65

Continuity of bilinear maps on direct sums of topological vector spaces - Glöckner, Helge (Journal of Functional Analysis)
Keywords: 46A03; 46A13; 46E10; 46F05

When unit groups of continuous inverse algebras are regular Lie groups - Glöckner, Helge; Neeb, Karl-Hermann (Studia Mathematica)
Keywords: 22E65; 34G10; 46H05

Data Mining and Decision Making - Meydani, Elnaz; Bahonar, Marziyeh; Gholami, Bahareh; Raeesi Vanani, Iman; Sohrabi, Babak (Advances in Business and Management. Volume 5)

Da sah ich mit Schrecken, daß sich die Welt um mich herum von A bis Z verwandelt hatte. Zur Verbindung von islamischer und romantischer Tradition in Orhan Pamuks "Das Neue Leben" - Schulte Eickholt, Swen (Islam in der deutschen und türkischen Literatur)

Rezension zu: „ ‘Und ihr wollt das Land besitzen?‘ (Ez 33,25): Ezechiels Umgang mit repräsentativen Redensarten“ - Bergmann, Claudia Dorit (CBQ)

Simulation of phase‐transformations based on numerical minimization of intersecting Gibbs energy potentials - Ostwald, Richard; Bartel, Thorsten; Menzel, Andreas (PAMM)
Abstract We present a novel approach for the simulation of solid to solid phase‐transformations in polycrystalline materials. To facilitate the utilization of a non‐affine micro‐sphere formulation with volumetric‐deviatoric split, we introduce Helmholtz free energy functions depending on volumetric and deviatoric strain measures for the underlying scalar‐valued phase‐transformation model. As an extension of affine micro‐sphere models [5], the non‐affine micro‐sphere formulation with volumetric‐deviatoric split allows to capture different Young's moduli and Poisson's ratios on the macro‐scale [1]. As a consequence, the temperature‐dependent free energy assigned to each individual phase takes the form of an elliptic paraboloid in volumetric‐deviatoric strain space, where the energy landscape of the overall material is obtained from the contributions of the individual constituents. For the evolution of volume fractions, we use an approach based on statistical physics–taking into account actual Gibbs energy barriers and transformation probabilities [2]. The computation of individual energy barriers between the phases considered is enabled by numerical minimization of parametric intersection curves of elliptic Gibbs energy paraboloids. (© 2012 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Phase-transformations interacting with plasticity – A micro-sphere model applied to TRIP steel - Ostwald, Richard; Bartel, Thorsten; Menzel, Andreas (Computational Materials Science)

Capacitance performance of cobalt hydroxide-based capacitors with utilization of near-neutral electrolytes - Fedorov, Fedor S.; Linnemann, Julia; Tschulik, Kristina; Giebeler, Lars; Uhlemann, Margitta; Gebert, Annett (Electrochimica Acta)
Conventional alkaline solutions used for capacitive performance of electrodeposited cobalt hydroxides have a number of disadvantages as they are corrosive, environmentally unfriendly and provide a small working potential range. In this study, the capacitive properties of electrodeposited cobalt hydroxide/oxide were investigated in 1 M Na2SO4 solution with pH 5.5 by means of cyclic voltammetry, galvanostatic charging/discharging experiments and electrochemical impedance spectroscopy. The capacitance of the cobalt hydroxide/oxide was demonstrated to have high values of 141 F g−1 at scan rate 8 mV s−1 in this 1 M Na2SO4 solution. The anodic potential range is extended by 0.8–1.3 V vs. Ag/AgCl. A good cyclic stability and reversibility were observed.
Keywords: electrodeposition; cobalt hydroxide; supercapacitors

2-Aminopyrimidine-silver(I) based organic semiconductors: Electronic structure and optical response - Riefer, A.; Rauls, E.; Schmidt, Wolf Gero; Eberhard, J.; Stoll, I.; Mattay, J. (Physical Review B)

The electronic structure and optical response of rutile, anatase and brookite TiO2 - Landmann, M; Rauls, E; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

pH-dependent structure and energetics of H2O/MgO(100) - Thissen, Peter; Thissen, Vera; Wippermann, Stefan; Chabal, Yves J.; Grundmeier, Guido; Schmidt, Wolf Gero (Surface Science)